6′-Fluoro-3-deazaneplanocin: Synthesis and antiviral properties, including Ebola. Issue 23 (15th December 2018) - Liu, Chong; Chen, Qi; Cardinale, Steven; Bowlin, Terry L.; Schneller, Stewart W.
Graphical abstract: Abstract: A convenient stereospecific synthesis of 6′-fluoro-3-deazaneplanocin (6 ) has been accomplished fromd -ribose in 15 steps. It is reported to possess significant activity towards Ebola (Zaire, Vero, μM: EC50 < 0.36; CC50 125; SI > 347) with moderate inhibition of the target enzyme (S-adenosylhomocysteine hydrolase), which did not correlate directly with its anti-Ebola effects. Compound6, with limited cytotoxicity, also displayed activity against measles, H1N1 and Pichinde.